1996
DOI: 10.1051/forest:19960246
|View full text |Cite
|
Sign up to set email alerts
|

Element analysis of tree rings in pedunculate oak heartwood: an indicator of historical trends in the soil chemistry, related to atmospheric deposition

Abstract: Summary — When investigating historical alterations of the soil chemistry, it could be interesting to determine the mineral content of the successive annual tree rings. The study reported here aimed at verifying this assumption. Oak heartwood was selected in order to minimize the disturbance due to element translocations in the wood. This study was carried out in a forest included in a floristic and edaphic survey performed earlier throughout northeast France. Xylem cores were extracted from the boles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
(40 reference statements)
3
27
1
1
Order By: Relevance
“…No element could be ascribed to the third category. In line with two previous studies [11,18], our results show that pedunculate oak sapwood is markedly richer than heartwood in N, P, K, Mg, Mn. Abrupt increases in mineral element concentrations at the heartwood/sapwood boundary are usually interpreted as resulting from nutrient resorption from senescing sapwood rings [2,6,14,16,18,23,25,27,31].…”
Section: Comparison Of Oak and Beechsupporting
confidence: 81%
See 3 more Smart Citations
“…No element could be ascribed to the third category. In line with two previous studies [11,18], our results show that pedunculate oak sapwood is markedly richer than heartwood in N, P, K, Mg, Mn. Abrupt increases in mineral element concentrations at the heartwood/sapwood boundary are usually interpreted as resulting from nutrient resorption from senescing sapwood rings [2,6,14,16,18,23,25,27,31].…”
Section: Comparison Of Oak and Beechsupporting
confidence: 81%
“…By contrast, Ca, Mg and Mn often have higher concentrations in the heartwood [27]. The particular pattern of element resorption found in Quercus robur in this study and by de Visser [11] and Lévy et al [18] is strikingly similar to that reported for other species of Quercus from Northern America (Q. rubra, Q. alba, Q. coccinea: [17,19,31,33]), China (Q. mongolica: [6]) and Japan (Q. mongolica, Q. serrata: [25]). Thus, it would appear that a high resorption of Ca, Mg, Mn, K, at the heartwood/sapwood boundary is a characteristic feature of most (if not all) species of Quercus.…”
Section: Nutrient Resorption In Oakmentioning
confidence: 45%
See 2 more Smart Citations
“…its absolute distance or age counted from the cambium, and the abundance of mineral inclusions differ considerably between trees, notably between trees I and II. Radial variations of the elementary mineral content found in oak wood have been attributed to differences in soil chemistry [18] and to soil acidification by atmospheric pollution [12]. Differences in soil nutrient factors appeared to play a major role in explaining the autecology of Q. petraea in northern France [1].…”
Section: Identification Localisation and Possible Causes Of Mineral mentioning
confidence: 99%